The relative strength of relations between different facets of teacher motivation and core dimensions of teaching quality in mathematics - A multilevel analysis. (December 2021) - Lazarides, Rebecca; Schiefele, Ulrich
Abstract: Teacher self-efficacy and teacher interest are two key facets of teacher motivation that are important for high-quality teaching. Little is known about the relative strength of the effects of teacher self-efficacy and interest on teaching quality when compared with one another. We extend previous research on teacher motivation by examining the relations linking mathematics teacher self-efficacy and interest with several relevant dimensions of teaching quality as perceived by teachers and students. Participants were 84 mathematics teachers (61.2% female) and their students (1718 students; 48.5% girls). Based on doubly latent multilevel models, we found that teacher-reported self-efficacy in instruction was positively related to teacher-reported cognitive activation, classroom management, and emotional support in mathematics classrooms. Teacher-reported educational interest showed positive associations with both student- and teacher-perceived emotional support. Future research is advised to focus more strongly on the unique relations between different teachers' motivational characteristics and relevant dimensions of teaching quality. Highlights: We used multilevel modeling with student and teacher data. Teacher self-efficacy related to teacher-reported teaching quality. Teacher educational interest related to teacher- and student-reported support. Teacher knowledge did not relate to teacher- or student-rated teaching quality.